The Tongue and the Reed: Organs and Instruments in the Philosophical Part of Hippocratic Regimen. (9th December 2014) - Demont, Paul
Abstract: In the first book of Hippocratic Regimen, an unclear excursus explains how the technai imitate, and thus allow us to understand, human nature. It is argued here that the new polysemy of the word organon at the beginning of the fourth century is utilized by the author in his comparison, that this observation allows new understandings of some difficult passages and that such polysemy applies to a specific organon, the glotta ('tongue' and 'reed').